2020
DOI: 10.1002/marc.202000304
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insights into the Mechanism of Heat‐Set Gel Formation of Polyisocyanopeptide Polymers

Abstract: One of the key factors influencing the mechanical properties of natural and synthetic extracellular matrices (ECM) is how large‐scale 3D gel‐like structures emerge from the molecular self‐assembly of individual polymers. Here, structural characterization using small‐angle neutron scattering (SANS) of ECM‐mimicking polyisocyanopeptide (PIC) hydrogels are reported as a function of background ions across the Hofmeister series. More specifically, the process of polymer assembly is examined by probing the structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…According to the previous study, 24 monovalent anion salts, such as NaCl and NaH 2 PO 4 could not induce the formation of hydrogel, and cations had no effect on the hydrogelation. Generally, the effect of ions on the gelation roughly followed the Hofmeister series: CO 3 2− > SO 4 2− > S 2 O 3 2− > H 2 PO 4 − > F − > Cl − > Br − ~ NO 3 − > I − > SCN − 36–38 . Therefore, we investigated the effect of Na 2 SO 3 on the gelation of TPGS 1000 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the previous study, 24 monovalent anion salts, such as NaCl and NaH 2 PO 4 could not induce the formation of hydrogel, and cations had no effect on the hydrogelation. Generally, the effect of ions on the gelation roughly followed the Hofmeister series: CO 3 2− > SO 4 2− > S 2 O 3 2− > H 2 PO 4 − > F − > Cl − > Br − ~ NO 3 − > I − > SCN − 36–38 . Therefore, we investigated the effect of Na 2 SO 3 on the gelation of TPGS 1000 .…”
Section: Resultsmentioning
confidence: 99%
“…According to the previous study, 24 monovalent anion salts, such as NaCl and NaH 2 PO 4 could not induce the formation of hydrogel, and cations had no effect on the hydrogelation. Generally, the effect of ions on the gelation roughly followed the Hofmeister series: [36][37][38] Therefore, we investigated the effect of Na 2 SO 3 on the gelation of TPGS 1000 . It could be found that TPGS 1000 easily formed gel with a translucent status under the condition of 4.5% Na 2 SO 3 (Table 1).…”
Section: The Effect Of Different Medium On Gelationmentioning
confidence: 99%
“…In addition to organic salts, heat-set gelation can also be exhibited by coordination polymers, , organic/biological polymers, inorganic complexes, and charge transfer complexes . None of these compounds melt or dissolve under conditions conducive to heat-set gelling.…”
Section: Heat-set Gelsmentioning
confidence: 99%
“…Heat-set gelators can also be designed by introducing long chains into coordination polymers . Biological polymer materials such as globular protein gel, polyisocyanopeptide polymers, quinoa protein, RuBisCO, konjac glucomannan, and polyurethane/PEG block copolymers can also form heat-set gels. …”
Section: Heat-set Gelsmentioning
confidence: 99%
“…In recent years, there has been an increased interest in polyisocyanide-based hydrogels for 3D cell culture due its stressinduced stiffening properties, collagen-like helical architecture and thermosensitive properties which allow for facile recovery of encapsulated cells. [277][278][279] Zhang et al developed a polyisocyanide-based hydrogel decorated with the adhesive RGD peptide to form mammary gland organoids. Not only did the hydrogels enable mammary gland organoid formation, the resulting organoids could be maintained for prolonged durations in vitro and retain their ability to branch.…”
Section: Reviewmentioning
confidence: 99%